Difficulties Faced by Iraqi Second Year Students in Learning Weak Forms - Adil Mekki, Tamara; Mohsin Rawdhan, Sammerah (Al-Adab Journal, 2020)
The current study aims at investigating difficulties encountered by Iraqi second year students in learning weak forms .Thus, the descriptive analytical approach has been adopted as well as three tools have been used for gathering data relating to the study, particularly a questionnaire production and recognition tests to second Year students of English at university of Baghdad-college of languages, department of English. The Iraqi second year students have difficulty in Learn weak forms due to the fact of intelligibility, syllables, and stress .Besides, the undergraduates students are unable to determine the number of syllables and they are unable to distinguish between the various words classes. Finally ,they lack stress placement and vowels reduction.